Implantable Drug Reservoir Devices for Inner Ear Delivery of Pharmacotherapeutics. (October 2020) - Kita, Ashley; Saldate, Johnny; Chang, Courtney; Chellappa, Nitika; Jong, Jeremy; Matsuda, Riley; Schmidt, Andrew; Shih, Brandon; Shafqat, Iram; Schoettler, Kari; Acharya, Shiv; Seidlits, Stephanie; et al.
Objective: Cisplatin is a platinum-based chemotherapeutic drug that secondarily induces toxicity in inner ear sensory epithelia, contributing to auditory and vestibular dysfunction. We describe the creation of a drug reservoir device (DRD) to combat this ototoxicity for the duration of chemotherapy. As ototoxic side effects of chemotherapy may limit an oncologist's ability to prescribe first-line agents such as cisplatin, mitigating such devastating effects through prolonged topical therapy would be tremendously valuable. Study Design: We investigated (1) the ability of an electrospun polylactic acid DRD to provide prolonged delivery of the posited otoprotectant metformin and (2) the development of an in vitro model utilizing Sh-Sy5y human neuroblastoma cells to assess the efficacy of metformin in reducing cisplatin-induced toxicity. Setting: Neurophysiology laboratory. Methods: Basic science experiments were performed to assess DRD properties and metformin's effects on cisplatin toxicity in culture. Results: We found that DRDs with increasing polylactic acid concentrations exhibited metformin release for up to 8 weeks. In modeling elution across the round window in vitro, continued elution of metformin was observed for at least 6 weeks, as quantified by spectrophotometry. Unfortunately, metformin did not exhibit protective efficacy in this model using Sh-Sy5y cells. Conclusion: While metformin was not found to be protective in Sh-Sy5y cells, these results suggest that an electrospun DRD can provide a tailorable drug delivery system providing medication for the duration of chemotherapy treatment. This represents a novel drug delivery system and efficacy screening assay with broad clinical applications in personalized delivery of inner ear therapies.